Pengaruh Model 3C3R Terhadap Kemampuan Literasi Sains Siswa Pada Konsep Interaksi Mahluk Hidup Dengan Lingkungan - Gendis Siti Rahmawati; Sistiana Windyariani; Suhendar Suhendar (Magister Pendidikan Biologi, Universitas Negeri Medan, 2019)
This study aims to determine how the influence of the 3C3R learning model (Content, Context, Connection, Reading, Reasoning, Reflecting) on students' literacy skills after learning in the concept of interaction between living things and the environment. The sample of this study was grade VII students in SMP Negeri 13 Kota Sukabumi which were taken using a pusposive sampling technique with 24 students in the experimental class and 25 students in the control class. The instrument of this research is a matter of testing scientific literacy skills. This type of research is Quasi Experimental with a non equivalent control group design research design. The data analysis technique uses the t test with a significance level of α 0.05. The results of the t test show (tcount 6.845> ttable 2.051) so that H0 is rejected and H1 is accepted, meaning that there are significant differences in students' scientific literacy skills between the experimental class and the control group. So it can be concluded that the 3C3R learning model influences students' scientific literacy abilities.